Fusing Crowdsourcing and Social Media to Harvest Volunteered and Ambient Geospatial Information - Kassahun, Mafkereseb; Worku, M.
Crowdsourcing is the process of getting work, idea or funding, usually online, from a crowd of people. The idea is to take intended tasks and outsource them to the crowd. On the other hand, social media are computermediated tools that allow people to create, share or exchange information, ideas, pictures and videos throughout virtual communities and social networks. Both crowdsourcing and social media play a great role as a source of AGI (Ambient Geospatial Information) and VGI (Volunteered Geospatial Information) for multiple geoapplications related to Agriculture, Health, Environmental studies, Tourism, and etc. VGI is purposely contributed by citizens via crowdsourcing platforms, whereas AGI is contributed by the public without explicit intention via social networks, such as Facebook, Twitter and Flickr. In this paper, we proposed a framework to fuse crowdsourcing and social media platforms to harvest both VGI and AGI for the aforementioned applications. Accordingly, the crowdsourcing platforms serve as sources of structured VGI, which can be used for the intended applications without further manipulation; and the social media platforms, which are photo sharing (Flickr), socializing (Facebook) or micro-blogging (Twitter) in kind, serve as sources of AGI, which demand further analyses and manipulations, as the contributions of information are not intentional. To this end, the proposed framework has a multi-strategy text processing and information retrieval methods that consume texts and photos from social media and harvest the required AGI, after which the VGI and AGI are integrated and stored in a common spatial database for later uses.